A companion to applied ethics - Frey, R. G. (Raymond Gillespie); Wellman, Christopher Heath (Blackwell companions to philosophy, 2003)
Applied or practical ethics is perhaps the largest growth area in philosophy today, and many issues in moral, social, and political life have come under philosophical scrutiny in recent years. Taken together, the essays in this volume - including two overview essays on theories of ethics and the nature of applied ethics - provide a state-of-the-art account of the most pressing moral questions facing us today. Provides a comprehensive guide to many of the most significant problems of practical ethicsOffers state-of-the-art accounts of issues in medical, environmental, legal, social, and business.